2023
DOI: 10.1002/mco2.282
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin inhibits circ0030018 to suppress glioma tumorigenesis via the miR‐1236/HER2 signaling pathway

Abstract: In the central nervous system diseases, glioma is one of the most common malignancies around the world. Despite the recent improvements in therapies for glioma, the prognosis of some high-risk glioma remains poor. In glioma, isoliquiritigenin (ISL) is reported to have antioxidative and antitumor activities. However, the potential mechanisms between ISL and circle RNAs (circRNAs) in the glioma tumorigenesis process have not yet been reported.Here, we treated glioma cells with ISL, and circRNA expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Our single-cell and GSEA analyses showed that MCM3 was closely linked to EMT, which to some extent explained the poor prognosis of LGG patients caused by MCM3 overexpression. In addition, previous studies have demonstrated that essential nodes in crucial pathways may be specifically blocked to slow glioma progression, which further suggests that MCM3 may be a promising therapeutic target for LGG ( Tang et al, 2014 ; Liu et al, 2023 ). In our clinical cohort, MCM3 expression was correlated with the clinical features and prognosis of patients with LGG.…”
Section: Discussionmentioning
confidence: 97%
“…Our single-cell and GSEA analyses showed that MCM3 was closely linked to EMT, which to some extent explained the poor prognosis of LGG patients caused by MCM3 overexpression. In addition, previous studies have demonstrated that essential nodes in crucial pathways may be specifically blocked to slow glioma progression, which further suggests that MCM3 may be a promising therapeutic target for LGG ( Tang et al, 2014 ; Liu et al, 2023 ). In our clinical cohort, MCM3 expression was correlated with the clinical features and prognosis of patients with LGG.…”
Section: Discussionmentioning
confidence: 97%
“…Among these mechanisms, small noncoding RNAs (ncRNAs) measuring [20][21][22][23][24] base pairs, such as miRNA, have been extensively investigated and are recognized as the most thoroughly studied regulators of gene expression in various diseases. [12][13][14][15][16][17] Recent research suggests that circRNA modulates gene expression more precisely than other types of ncR-NAs. 18,19 Typically, circRNAs can join forces with RNA-binding proteins (RBPs) (Figure 1) to form protein complexes that control the transcriptional and parental linear genes' post-transcriptional expression.…”
Section: Epilepsy and Circrnamentioning
confidence: 99%
“…Numerous epigenetic regulatory mechanisms effectively govern the genes implicated in epileptogenesis, and their enduring alteration in the hippocampus may exert a substantial influence on TLE. Among these mechanisms, small noncoding RNAs (ncRNAs) measuring 20–24 base pairs, such as miRNA, have been extensively investigated and are recognized as the most thoroughly studied regulators of gene expression in various diseases 12–17 . Recent research suggests that circRNA modulates gene expression more precisely than other types of ncRNAs 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing body of research that has shed light on the significant contribution of non-coding RNAs to the pathogenesis of different types of cancers ( Wu J. et al, 2022 ; Gao et al, 2022 ; Liu et al, 2023 ; Xie et al, 2023 ). Specifically, lncRNAs and the JAK-STAT pathway have emerged as pivotal factors in the initiation and advancement of CRC ( Li B. et al, 2022 ).…”
Section: Future Prospectsmentioning
confidence: 99%